2021
DOI: 10.1101/2021.02.02.429442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PDE9 Inhibition Activates PPARα to Stimulate Mitochondrial Fat Metabolism and Reduce Cardiometabolic Syndrome

Abstract: Central obesity with cardiometabolic syndrome (CMS) is a major global contributor to human disease, and effective therapies are needed. Here, we show inhibiting cyclic-GMP selective phosphodiesterase-9A (PDE9-I) suppresses established diet-induced obesity and CMS in ovariectomized female and male mice. PDE9-I reduces abdominal, hepatic, and myocardial fat accumulation, stimulates mitochondrial activity in brown and white fat, and improves CMS, without altering activity or food intake. PDE9 localizes to mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
2
1
0
Order By: Relevance
“…Most importantly, current studies indicate they are safe and well tolerated in humans ( 28 34 ). Moreover, analogous to what we show in this study with Pde9a −/− mice, our collaborators have found that the PF PDE9 inhibitor reduces body weight by increasing energy expenditure and thereby improves glucose handling in a model of cardiometabolic disease ( 50 ). Comparable to our findings, the results of Mishra et al ( 50 ) show that PDE9 inhibition is associated with increased respiration and expression of thermogenic genes including Ucp1 ( 50 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Most importantly, current studies indicate they are safe and well tolerated in humans ( 28 34 ). Moreover, analogous to what we show in this study with Pde9a −/− mice, our collaborators have found that the PF PDE9 inhibitor reduces body weight by increasing energy expenditure and thereby improves glucose handling in a model of cardiometabolic disease ( 50 ). Comparable to our findings, the results of Mishra et al ( 50 ) show that PDE9 inhibition is associated with increased respiration and expression of thermogenic genes including Ucp1 ( 50 ).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, analogous to what we show in this study with Pde9a −/− mice, our collaborators have found that the PF PDE9 inhibitor reduces body weight by increasing energy expenditure and thereby improves glucose handling in a model of cardiometabolic disease ( 50 ). Comparable to our findings, the results of Mishra et al ( 50 ) show that PDE9 inhibition is associated with increased respiration and expression of thermogenic genes including Ucp1 ( 50 ). Together, these observations suggest that PDE9 inhibitors can increase thermogenic gene expression in adipocytes via increasing PKG signaling, and these therapeutic implications may be translatable to humans.…”
Section: Discussionsupporting
confidence: 86%
“…A multitude of trials have studied the effects of up-regulating cGMP synthesis through inorganic nitrates in HFpEF or of other agents such as soluble guanylate cyclase stimulators (eg, vericiguat, praliciguat) ( 56 , 57 , 58 ). In addition, the effects of phosphodiesterase type 5 and 9 inhibition have also been investigated ( 59 , 60 ). To date, however, none of these pathways has shown clinical benefit in patients with HFpEF.…”
Section: Advancements In Therapeutic Options For Hfpefmentioning
confidence: 99%